Financial Management of MSMEs in Cirebon Regency: A Qualitative Approach in Improving Performance and Sustainability - Rina Destiana; Acep Komara (Yayasan Adra Karima Hubbi, 2024)
ABSTRACT Background. Effective financial management is a crucial aspect for Micro, Small, and Medium Enterprises (MSMEs) in Cirebon Regency in achieving optimal performance and business sustainability. With the existence of MSMEs that contribute significantly to the regional economy, a deep understanding of financial management is very important. Purpose. This research aims to explore the financial management practices of MSMEs through a qualitative approach, analyze the challenges faced, and identify strategies that can be applied to improve financial management. Method. This study applies a qualitative approach to explore the financial management practices of MSMEs in Cirebon Regency. Participants consisted of 20 MSME owners who manage businesses in the food and beverage, handicraft, and trade sectors, with a minimum of two years of experience. Data were collected through in-depth interviews and observations. The interviews use a semi-structured guide to obtain information about financial management practices, challenges faced, and strategies implemented, conducted directly at the business site to provide better context. Observations are carried out to understand daily financial management practices, including recording transactions and interactions with customers. The data obtained was analyzed using a thematic analysis approach. The analysis process begins with the transcription of interviews and recording of observations, followed by the identification of the main themes that emerge and their grouping into relevant categories. The results of the analysis are expected to provide in-depth insights into the financial management of MSMEs in Cirebon Regency. Results. The study show that many MSMEs in Cirebon Regency experience difficulties in financial management due to low financial literacy, lack of good financial planning, and lack of access to support from financial institutions. Conclusion. Effective financial management is very important for the performance and sustainability of MSMEs in Cirebon Regency. This article recommends the need for intensive education and training programs for MSMEs to improve their financial management skills.